Assessment of Rutting Resistance of Asphalt Mixtures Incorporating Recycled Concrete Aggregate After Treatment - Ghufran Abd AL–Muhson Hussen; Mohammed Qadir Ismael (Journal of Engineering)
Perpetual research endeavors have been created within the existing research to improve the sustainability elements concerning the road structure sector, i.e., minimize possible pollutants and improve monetary profitability. This study aims to determine how recycled concrete aggregates (RCA), which come from tearing down buildings, affect rutting performance using specimens prepared in a laboratory. Four replacement proportions (0, 25, 50, 75)% were studied for the coarse portion of natural aggregate. RCA was treated by immersing it in hydrochloric acid (HCL). The surface morphology of treated RCA was investigated using a scanning electron microscopy (SEM) test. This study employed two preliminary assessments: the typical Marshall test to find the ideal asphalt content and explore the volumetric properties of asphalt mixes. The other exam was the wheel-tracking assessment. A four asphalt concrete slab sample was placed under repeated wheel loads of 700 N at 55°C to determine its resistance to cracking and rutting. An investigation revealed that mixed with RCA content of 75%, rut depth is higher at 11.83%.